The Ethical Dilemmas Associated with Working in an Immigration Removal Centre. (June 2013) - Allen, Danny
The purpose of this paper is to share with colleagues some of the ethical problems encountered in working in an environment unfamiliar to the vast majority of psychiatrists. The author, a consultant psychiatrist with 17 plus years' experience in the NHS, spent a year working part-time in Colnbrook Immigration Removal Centre; an institution holding just over 300 men who are held in administrative detention for periods of time ranging from days to years pending decisions on their immigration status. About 50% of these men have criminal records and the turnover of detainees is fast and unpredictable. The paper describes some of the everyday ethical problems encountered by the author together with some background to the working environment and attempts to tease out some of the key pillars upon which the doctor's work is based in order to inform the limitations and challenges she/he faces.